Research progress in the development of natural-product-based mucosal vaccine adjuvants - Gao, Yingying; Guo, Ying (Frontiers in Immunology, 2023)
Mucosal vaccines have great potential and advantages in preventing infection caused by multiple pathogens. In developing mucosal vaccines, the biggest challenge comes from finding safe and effective adjuvants and drug delivery systems. Great progress has been made in the generation of mucosal adjuvants using detoxified bacterial toxin derivatives, pathogen-related molecules, cytokines, and various vaccine delivery systems. However, many problems, relating to the safety and efficacy of mucosal vaccine adjuvants, remain. Certain natural substances can boost the immune response and thus could be used as adjuvants in vaccination. These natural-product-based immune adjuvants have certain advantages over conventional adjuvants, such as low toxicity, high stability, and low cost of production. In this review, we summarize the latest natural-product-based immune adjuvants, and discuss their properties and clinical applications.